Simpatía y humanismo en las ideas estéticas de Enrique José Varona / Sympathy and humanism in aesthetic ideas of Enrique José Varona (Islas, 2021)
Este trabajo profundiza en una arista poco investigada delpensador cubano Enrique José Varona: sus ideas estéticas. Toma comohilos conductores dos núcleos temáticos fundamentales: Primeramenteaborda los principios básicos del humanismo en la modernidad. Seguidamenteintroduce la comprensión filosófica de simpatía; señala un grupode connotaciones éticas y estéticas de esta categoría en el pensamientooccidental de los siglos xviii y xix. Con respecto al pensamiento de EnriqueJosé Varona, se determinan rasgos humanistas en su reflexión estética,en relación con el contexto occidental y cubano. Se valora el papel de laconcepción de simpatía de Varona en el conjunto de sus ideas estéticas,y en el contenido humanista de las mismas. Se analiza la relación entrela educación estética, la simpatía y la moral.This research goes more deeply into an aspect of Enrique JoséVarona, which has little been researched: his aesthetic ideas. The paperis based on two main topics. First, it focuses on humanism and its mainprinciples, as a set of ideas which stress the human being dignity andthe search of its harmonic development. Later, the paper presents thephilosophical understanding of sympathy, and shows a group of ethicaland aesthetic connotations of such category in the Western thinking of18th and 19th centuries. With respect to Enrique José Varona´s thought,some humanistic features are determined in his aesthetic ideas, related tothe Western and Cuban context. The role of Varona´s sympathy conceptwith his aesthetic ideas as well as their humanistic content is assessed.The relationship among aesthetic education, sympathy and ethical valuesis also studied.
Keywords: ideas estéticas de Enrique José Varona; humanismo en la modernidad; educación estética; aesthetic ideas of Enrique José Varona; humanism in modernity; aesthetic Education